2021
DOI: 10.21037/atm-20-6710
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation is associated with inferior disease control and survival in stage III non-small cell lung cancer

Abstract: Background: The systemic immune-inflammation index (SII) correlates with patient survival in various types of solid malignancies, including non-small cell lung cancer (NSCLC). However, limited information is available on the prognostic implication and disease-specific survival of SII in patients undergoing definitive chemoradiation therapy (CRT) for stage III NSCLC.Methods: We retrospectively reviewed 125 patients who underwent curative intent CRT for stage III NSCLC with sufficient laboratory assessment from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Since most of the studies usually lean on surgery and/or chemotherapy as treatment modalities, we focused our attention in the literature on the studies on patients who were subjected to radiotherapy, as our aim is to make a comparison with the results of our study. All series had a retrospective design and included patients with locally advanced NSCLC treated with curative radiotherapy 1,23–28 . The inferences obtained can be listed as follows: First, these indices were often examined individually in published studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since most of the studies usually lean on surgery and/or chemotherapy as treatment modalities, we focused our attention in the literature on the studies on patients who were subjected to radiotherapy, as our aim is to make a comparison with the results of our study. All series had a retrospective design and included patients with locally advanced NSCLC treated with curative radiotherapy 1,23–28 . The inferences obtained can be listed as follows: First, these indices were often examined individually in published studies.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the studies examined the prognostic effects of indices on OS and PFS. LRRFS was not often added as study endpoint 23,27,28 . These studies yielded different results.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is linked to the progression of COVID-19 disease, systemic inflammation is a hallmark of moderate-tosevere COVID-19 disease [51] , which leads to an excessive inflammatory response of the innate and adaptive immune systems, termed Cytokine Release Syndrome (CRS) [52] . Inflammation is also an important part of the tumor environment and plays an important role in the development and progression of malignant tumors [53] . Cancer patients, as one of the most susceptible populations, are facing severe disadvantages during the COVID-19 epidemic, lung cancer patients, in particular [54] , have been reported to be more susceptible to SARS-Cov-2 infection and they are at higher risk of developing pneumonia and severe complications of COVID-19 on admission [55] .…”
Section: Table 4: Molecular Docking Of Colchicine With Core Target Pr...mentioning
confidence: 99%
“…Katayama et al ( 25 ) found that in bladder cancer, preoperative SII can identify non-muscle invasive bladder cancer patients who have worse disease and prognosis. Keit et al ( 26 ) also found that high SII was associated with low disease control and survival rate of stage III non-small cell lung cancer. However, whether it is associated with recurrent metastasis in GIST has not been reported in a large sample of studies.…”
Section: Introductionmentioning
confidence: 95%